A review of Bruton's tyrosine kinase inhibitors in multiple sclerosis - Airas, Laura; Bermel, Robert A.; Chitnis, Tanuja; Hartung, Hans-Peter; Nakahara, Jin; Stuve, Olaf; Williams, Mitzi J.; Kieseier, Bernd C.; Wiendl, Heinz (Sage, 2025)
Bruton's tyrosine kinase (BTK) inhibitors are an emerging class of therapeutics in multiple sclerosis (MS). BTK is expressed in B-cells and myeloid cells, key progenitors of which include dendritic cells, microglia and macrophages, integral effectors of MS pathogenesis, along with mast cells, establishing the relevance of BTK inhibitors to diverse autoimmune conditions. First-generation BTK inhibitors are currently utilized in the treatment of B-cell malignancies and show efficacy in B-cell modulation. B-cell depleting therapies have shown success as disease-modifying treatments (DMTs) in MS, highlighting the potential of BTK inhibitors for this indication; however, first-generation BTK inhibitors exhibit a challenging safety profile that is unsuitable for chronic use, as required for MS DMTs. A second generation of highly selective BTK inhibitors has shown efficacy in modulating MS-relevant mechanisms of pathogenesis in preclinical as well as clinical studies. Six of these BTK inhibitors are undergoing clinical development for MS, three of which are also under investigation for chronic spontaneous urticaria (CSU), rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Phase II trials of selected BTK inhibitors for MS showed reductions in new gadolinium-enhancing lesions on magnetic resonance imaging scans; however, the safety profile is yet to be ascertained in chronic use. Understanding of the safety profile is developing by combining safety insights from the ongoing phase II and III trials of second-generation BTK inhibitors for MS, CSU, RA and SLE. This narrative review investigates the potential of BTK inhibitors as an MS DMT, the improved selectivity of second-generation inhibitors, comparative safety insights established thus far through clinical development programmes and proposed implications in female reproductive health and in long-term administration.